The Call to Unity in a Time of the Uma Turmoil - Abdul Razzaq Hadafmand; Nasir Ahmad Sharaiti; Mohammad Safa Karim (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2026)
I present this article, entitled "A Call for Unity in a Time of Turmoil for the Muslim World," to readers in the Islamic world. In these particular circumstances, Islamic unity is a necessity dictated by the decline of the Muslim world, its humiliation, the fragmentation of its opinions, the disunity of its people, and its weakened strength on all political, economic, and military levels. Undoubtedly, the unity of Muslims faces numerous obstacles and formidable challenges that must be acknowledged and addressed in order to overcome them by finding solutions and ways out. Islamic unity is the only option for the Muslim world to emerge from these crises. The objectives of this topic include demonstrating the unity of the Muslim Ummah in the face of contemporary challenges, clarifying the impact of division and discord on the weakness and decline of the Ummah, calling for adherence to the Quran and Sunnah as the foundation of unity, consolidating the principle of Islamic brotherhood, rejecting fanaticism and reprehensible discord, highlighting the role of scholars and thinkers in guiding the Ummah towards unity, spreading awareness of the importance of cooperation and mutual support among members of the Muslim community, warning against sedition and conflicts that lead to fragmentation, and emphasizing that unity is the path to strength, honor, and stability. The importance of this topic stems from the numerous verses and hadiths that prohibit division and command unity and harmony. Its significance at this time lies in the fact that it is one of the major issues that has preoccupied the Muslim world for a long period. Therefore, one of the greatest forms of jihad is striving to unite the hearts of Muslims and bring them together on their religion and their religious and worldly interests, thus uniting their individuals and nations. The methodology of this research includes relying on the inductive method by collecting relevant texts from the Holy Quran and the Prophetic Sunnah related to unity and the rejection of division; employing the analytical method to interpret these texts and clarify their implications for the obligation of unity and the dangers of division; utilizing the comparative method by citing the opinions of scholars and highlighting points of agreement and disagreement regarding the concept of unity and its parameters; employing the historical method by referencing examples from the nation's history during periods of strength and weakness, and the impact of unity and division; utilizing the realistic method by connecting religious texts to the contemporary reality of the nation and analyzing the causes of instability; relying on scholarly documentation by citing authoritative sources and references for each issue; and organizing the research according to a clear scientific methodology that begins with definitions, then evidence, then applications, and finally conclusions.